Pembagian Harta Bersama Pasca Perceraian Terhadap Kontribusi Isteri Sebagai Pencari Nafkah (Studi Komparasi di Australia, Malaysia dan Jepang) - Sutini, Wiwin; Eka Trisna Dewi, Putu (Jurnal Aktual Justice, 2021)
Conjugal Property (Matrimonial Property) is a property that gained during the marriage beyond gift or inheritance, or in other words is a property and income generated by both spouse during the marriage. In accordance with the Indonesian 1974 Marriage Law, the rules for conjugal property disseverance is ½ regardless of who has a greater contribution in obtaining it. But gradualluy, it didn’t fulfill the sense of justice for a wife who has a dual role, provide the household necessities and manage the household affairs the best she can. The research method used in this research is a normative research type by using a literature study and using a comparative study approach. So, the judges in Indonesia have consider the contribution of husband and wife in obtaining conjugal property before make a verdict (a decision made after a lot of considering). The proportional contribution in conjugal property based on each role can be considered as a form of fulfilling the principle of justice for a wife who plays a dual role. Hopefully in the future, the proportional of conjugal property not only stagnate in ½, but can be distributed in 1/3: 2/3, 1/4, 3/4, etc